Et hic est finis : Bibliomanie, ou le livre-arbitre - Magali Soulatges (Flaubert: Revue Critique et Génétique)
A novelistic appropriation of a trial records? Variations on Nodier’s Bibliomaniac? A Hoffmann tale with a Dantesque hero? A physiology of the bibliophile? A clinical study of the bibliomaniac? Bibliomania, written by Flaubert when he was fifteen, is a literary curiosity with an open generic identity. The question of the esthetic status of this early story (that may be too hastily classified in the sole fantastic tale category) seems to be crystallized in a naïve image, endlessly contemplated by the tale’s hero: the one, around the word “Finis”, that forms the colophon of an ancient manuscript. On the grounds of the bibliomaniac Giacomo’s boundless worship of this image, and considering the possible double interpretation of the word “Finis” in bibliological and philosophical registers, might we not recognize in Bibliomanie the form of a Vanity?